2018
DOI: 10.1016/j.biocel.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the interplay between senescent dermal fibroblasts and cutaneous squamous cell carcinoma cell lines at different stages of tumorigenesis

Abstract: Cutaneous Squamous Cell Carcinoma (cSCC) is the second most common type of non-melanoma skin cancer in white-skinned populations. cSCC is associated with sun exposure and aging, which is concomitant with an accumulation of senescent cells in the skin. The involvement of senescent cells in carcinogenesis has been highlighted in several cancer types and an interaction between cSCC cells and senescent cells is proposed, but still little explored. Tumor-associated effects are mostly attributed to the senescence-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Irrespective of this, the data shows that the clock not only accurately captures aging in vivo but also models processes that define aging in vitro, adding to its utility. The sensitivity of the model towards senescence also delivers one potential mechanism explaining the pronounced age acceleration predicted by the model for the AK and SCC signatures, as an accumulation of senescent cells is not only a feature of aging tissues but also frequently observed in precancerous and cancerous lesions, including AKs and SCCs 47 , 48 .…”
Section: Resultsmentioning
confidence: 94%
“…Irrespective of this, the data shows that the clock not only accurately captures aging in vivo but also models processes that define aging in vitro, adding to its utility. The sensitivity of the model towards senescence also delivers one potential mechanism explaining the pronounced age acceleration predicted by the model for the AK and SCC signatures, as an accumulation of senescent cells is not only a feature of aging tissues but also frequently observed in precancerous and cancerous lesions, including AKs and SCCs 47 , 48 .…”
Section: Resultsmentioning
confidence: 94%
“… 70 The NF‐κB‐activated SASP factors, such as IL‐6, IL‐8 and MMPs, induce paracrine DNA damage, chronic inflammation and senescence of healthy neighbouring cells, resulting in acceleration of ageing. 71 , 72 , 73 Therapeutic inhibition of overexpressed SASP factors (IL‐6, IL‐8, MMP‐1 and MMP‐9) of senescent HDFs could reverse inflammatory response and promote skin rejuvenation. 74 , 75 , 76 By using P65 blocker (P65 siRNA) and P65 agonist (prostratin), this study confirmed the NF‐κB pathway‐dependent anti‐ageing mechanism of hPL.…”
Section: Discussionmentioning
confidence: 99%
“…SASP is the main characteristics of cellular senescence, containing specific pro‐inflammatory and senescence messaging secretome 70 . The NF‐κB‐activated SASP factors, such as IL‐6, IL‐8 and MMPs, induce paracrine DNA damage, chronic inflammation and senescence of healthy neighbouring cells, resulting in acceleration of ageing 71–73 . Therapeutic inhibition of overexpressed SASP factors (IL‐6, IL‐8, MMP‐1 and MMP‐9) of senescent HDFs could reverse inflammatory response and promote skin rejuvenation 74–76 .…”
Section: Discussionmentioning
confidence: 99%
“…While in physiologic conditions, they are almost resting, in the presence of any skin injury, they show abnormalities in the metabolism and proliferation, which can be at the basis of aging skin structure changes [30,31]. Even more relevant is the involvement of the senescent fibroblasts not only in the early stages of skin carcinogenesis [32] but also in cancer cell migration and metastasis, both in melanoma [33] and in NMSC [34]. Therefore, the preservation of their functionality can be a strategy in the prevention of intrinsic and extrinsic skin aging and even cutaneous carcinogenesis [35,36].…”
Section: Discussionmentioning
confidence: 99%